Projections of Mukai varieties - Kapustka, Michał (Mathematica Scandinavica, 2018)
This note is an answer to a problem proposed by Iliev and Ranestad. We prove that the projections of general nodal linear sections of suitable dimension of Mukai varieties M_g are linear sections of M_g-1.